Experience with transplantation of human cryopreserved ovarian tissue to a sub-peritoneal abdominal site. Issue 9 (12th July 2021) - Gook, Debra; Hale, Lyndon; Polyakov, Alex; Manley, Tom; Rozen, Genia; Stern, Kate
Abstract: STUDY QUESTION: Is a sub-peritoneal abdominal site a suitable site for cryopreserved ovarian tissue transplantation? SUMMARY ANSWER: Live births have resulted from oocytes aspirated from follicles within cryopreserved ovarian tissue transplanted in a sub-peritoneal abdominal site with similar outcomes observed in terms of number of mature oocytes recovered and embryo development from tissue transplanted to sub-peritoneal abdominal, ovarian, and pelvic sites in our clinic. WHAT IS KNOWN ALREADY: Over 130 live births have been reported from cryopreservation of ovarian tissue and subsequent transplantation. In the majority of these, tissue was transplanted onto the remaining ovary. Although grafting to a non-ovarian, non-pelvic, sub-peritoneal abdominal site has resulted in births, it has been suggested that compromised outcomes may be expected from a non-pelvic site. STUDY DESIGN, SIZE, DURATION: The aim of the study was to assess the outcome from cryopreserved ovarian tissue transplanted to a site out of the pelvic area; a sub-peritoneal abdominal site. These outcomes were compared to transplantation to the ovary and peritoneal pelvic area in a cohort of 17 fertility preservation women where the individual sites of follicle aspiration were known and subsequent outcomes tracked. Ovarian tissue was slow frozen using the cryoprotectants propanediol and sucrose (n = 16 women) or using dimethyl sulfoxide and sucrose (n = 1 woman). Tissue was kept at 4°C overnight prior to freezing for 1 case. Tissue was thawed appropriately and prepared on 6.0 vicryl sutures for transplantation. Tissue was placed laparoscopically into a sub-peritoneal abdominal site, a pelvic side wall peritoneal pocket and the ovary. PARTICIPANTS/MATERIALS, SETTING, METHODS: Following resumption of cycling, gonadotrophin stimulation commenced with FSH, LH and antagonist and a trigger was given when one follicle was >13 mm in diameter. Abdominal follicles were aspirated under ultrasound guidance trans-abdominally; ovarian and pelvic follicles were aspirated trans-vaginally. Due to an inability to differentiate pelvic from ovarian follicles at the time of ultrasound-guided oocyte retrieval, both were classified as ovarian on the side where both were present. However, on the side, where no ovary was present, outcomes from pelvic follicles were reported. MAIN RESULTS AND THE ROLE OF CHANCE: Average time lapse between ovarian tissue harvest and graft was 6 years. Resumption of cycling occurred on average 4.2 months post first graft, regardless of graft site. Mean follicle diameter on the day of oocyte aspiration was 14 mm for all sites. Aspiration failed to retrieve an oocyte in 30% (36/120) of abdominal follicles which was similar to the other sites; ovarian 24% (21/87), pelvic 32% (31/97). A similar proportion of retrieved oocytes was mature from all sites (67% (50/75) abdominal, 68% (42/62) ovarian, 59% (34/58) pelvic). The proportion of embryos which developed on Day 2 from those fertilized was also similar in all groups (90% (34/38) abdominal, 76% (22/29) ovarian, 96% (22/23) pelvic). To our knowledge, this is the first report of outcomes from cryopreserved ovarian tissue transplanted to a sub-peritoneal abdominal site and the subsequent comparison to outcomes from the ovary and a sub-peritoneal pelvic graft, within the same cohort of patients, where tissue was slow frozen predominantly with the cryoprotectant propanediol and sucrose. LIMITATIONS, REASONS FOR CAUTION: The study reports outcomes from a small number of women following ovarian tissue transplantation. Follicle density is an estimate only and the amount of tissue grafted varied between patients. WIDER IMPLICATIONS OF THE FINDINGS: The demonstration of successful outcomes from cryopreserved ovarian tissue grafted to a sub-peritoneal abdominal site has significant implications for the management of women in which grafting to pelvic sites is contraindicated although it appears to be important to trigger follicle maturation at a lower than normal follicular diameter. The relative ease of oocyte retrieval at the sub-peritoneal abdominal site also has positive implications for the introduction of this approach into clinical practice. STUDY FUNDING/COMPETING INTEREST(S): No specific funding was used. All authors have no conflict of interest. TRIAL REGISTRATION NUMBER: N/A.